Pengembangan Buku Ajar PAI Berbasis Mind Mapping untuk Meningkatkan Belajar Siswa Kelas XI di SMK Plus Umar Zahid Semelo Jombang - Maslachah, Ikfina; Shofiyani, Amrini (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research is motivated by the lack of variaty in learning concepts and the PAI textbooks used. Educators are often fixated on textbooks at school and the learning methods used only emphasize the concept of mastering the material. Therefore, the aim of this research is to determine the development and effectiveness of mind mapping-based PAI textbook product at SMK Plus Umar Zahid, especially in class XI to overcome existing problems. The method applied in this research is research and development (R&D) using the step model from Borg and Gell. The subjects in this research are one material and media expert and 30 class XI students. The data instruments used are interviews, questionnaires and tests. The results of the data analyzed produces are qualitative and quantitative data which includes: 1) Researchers have developed a mind mapping-based PAI textbook product, 2) Mind mapping-based PAI textbooks meet the validity criteria of very valid with an average rating of 83% and meet the eligibility criteria. suitable for use with an average of 78.3%, 3) From the results of the assessment of pre-test and post-test questions using SPSS, it shows that there are significant differences, and learning outcomes increase after using the developed product.